Planning for fauna-sensitive road design: A review - Johnson, Christopher D.; Matthews, Tony; Burke, Matthew; Jones, Darryl (Frontiers in Environmental Science, 2022)
Roads can have significant negative impacts on wildlife. Fauna-sensitive road design (FSRD) can alleviate adverse impacts on several species by installing specialised structures, such as wildlife crossing structures. This developing subfield has generally, however, had a limited impact on transportation planning and management. Indeed, most research is focused narrowly on technological solutions, instead of broader policy learnings. This systematic quantitative literature review (SQLR) of international literature sought to identify the biodiversity concerns acknowledged in transport planning policy, as well as the barriers to the adoption of environmental policies within transport planning. Despite considerable literature available on the impacts of roads on wildlife elsewhere, acknowledgement and consideration of both fauna movement and fauna-sensitive road design were limited in road transportation planning research. More broadly, failure to achieve environmental objectives within transport planning occurred primarily as a result of competing sector interests (conflicted knowledge), different political objectives (political interest), and incorrect interpretation of policies. In essence, the results add new layers of understanding to the field of transportation planning and policy, in particular, the gaps in acknowledgement of wildlife movements and the limitations of current fauna-sensitive road design considered. Importantly, the review identified multiple ecological support tools available to transport policy- and decision-makers. Integration of these in road transportation projects could facilitate enhanced uptake and adoption of FSRD measures and thus foster improved sustainability of the transport network.